Analisis Peran Kepemudaan terhadap Pengembangan Wilayah Kota Langsa Ditinjau dari Perspektif Geografi Sosial - Tengku Muhammad Sahudra (Universitas Negeri Medan, 2019)
The problem of developing cities/cities in Indonesia is characterized by differences in phenomena, among others in terms of population growth, the structure of work, education, transportation, and the increase in the number of buildings. The problem of development in Langsa City is caused by development planning that prioritizes physical development rather than non-physical (social) development. Population growth requires the development of facilities and infrastructure and development. Population growth can be caused by natural population growth and migration flows. The method in this study uses descriptive analysis and uses multiple linear regression analysis. The population in this study is that all Langsa City youths who have age 17-30 years are 29,034 people, while the sample is 99.65 people and rounded up to 100 respondents. The research results show that dynamic variables, catalysts, motivators, and innovators have a significant positive effect on the development of the Langsa City area from the perspective of social geography, while the evaluator variables have a positive and insignificant effect on the development of the Langsa City region from a social geography perspective.